Feasibility study of an electrodialysis system for in-home water desalination in urban India. (2017) - Nayar, Kishor G.; Sundararaman, Prithiviraj; O'Connor, Catherine L.; Schacherl, Jeffrey D.; Heath, Michael L.; Gabriel, Mario Orozco; Shah, Sahil R.; Wright, Natasha C.; Winter, V, Amos G.
Abstract: Poor quality of drinking water delivered to homes by state utilities, and a large reliance on brackish ground water resources in parts of urban India, has resulted in the adoption of in-home water treatment solutions. The only existing in-home water treatment solution capable of desalination is reverse osmosis (RO). However, existing RO products can recover only 25–50% of the feed water supplied as usable product water. In this study, an alternative solution that relies on electrodialysis (ED) was designed and experimentally shown to achieve a recovery of 80%, producing 12 L/h of water at the desired salinity of 350 ppm from a feed salinity of 3000 ppm. The cost and size of the proposed system were also found to be comparable to existing in-home RO systems. In-home ED water treatment systems could compete with existing RO products while providing the advantage of improved water-conservation in water-stressed India.